Perception and Readiness of Nursing Lecturers on Interprofessional Education - Sukaesih, Nunung Siti; Sopiah, Popi; Lindasari, Sri Wulan; Lindayanti, Emi; Pramajati, Hikmat; Danismaya, Irawan; Burdahyat, Burdahyat (Fakultas Ilmu-ilmu Kesehatan, 2022)
ABSTRACT Interprofessional education (IPE) has received increasing attention in the last ten years, and this is because patients need better health services, and health problems are increasingly complex. The Interprofessional team consists of professionals from various health sciences who have specific knowledge, attitudes, skills, and abilities. They have particular goals based on the patient's health care needs. Not all these health workers received good enough IPE when they went to school. In this study, researchers will examine the readiness and perceptions of lecturers in nursing faculty regarding IPE. There are several reasons why the IPE is necessary. This study aims to explore more deeply the perceptions and readiness of nursing lecturers regarding IPE implementation in nursing education. This study used a descriptive comparative and correlational design. The survey had responses from nursing lecturers (n = 53). The total lecturer's scores of RIPLS were high, with a mean score of 75.17 (SD=5.01) and a mean score of 74.55 (SD=8.27) of the IEPS total scores. When comparing the demographic data with the total scores of RIPLS and IEPS quantitatively, there were no significant differences. Also, statistically significant correlations were found between RIPLS and IEPS (p >0.0001). Keywords: Interprofessional Education (IPE); nursing; perception; readiness ABSTRAK Pendidikan interprofessional (IPE) mendapat perhatian yang semakin meningkat dalam sepuluh tahun terakhir, dan ini karena pasien membutuhkan pelayanan kesehatan yang lebih baik, dan masalah kesehatan yang semakin kompleks. Tim Interprofessional terdiri dari para profesional dari berbagai ilmu kesehatan yang memiliki pengetahuan, sikap, keterampilan, dan kemampuan tertentu. Mereka memiliki tujuan tertentu berdasarkan kebutuhan perawatan kesehatan pasien. Tidak semua tenaga kesehatan tersebut mendapatkan IPE yang cukup baik saat mereka bersekolah. Dalam penelitian ini, peneliti akan mengkaji kesiapan dan persepsi dosen di fakultas keperawatan tentang IPE. Ada beberapa alasan mengapa IPE diperlukan. Penelitian ini bertujuan untuk menggali lebih dalam persepsi dan kesiapan dosen keperawatan terhadap penerapan IPE dalam pendidikan keperawatan. Penelitian ini menggunakan desain deskriptif komparatif dan korelasional. Survei tersebut mendapat tanggapan dari dosen keperawatan (n = 53). Nilai otal RIPLS dosen tinggi, dengan rerata skor 75.17 (SD=5.01) dan rerata skor 7.,55 (SD=8.27) dari total skor IEPS. Jika membandingkan data demografi dengan total skor RIPLS dan IEPS secara kuantitatif, tidak ada perbedaan yang signifikan. Juga, korelasi yang signifikan secara statistik ditemukan antara RIPLS dan IEPS (p=0,0001). Kata kunci: Pendidikan Interprofessional (IPE); keperawatan; persepsi; kesiapan